Formulation of snack bars made from black rice bran (Oryza sativa L.) and sweet potato flour (Ipomoea batatas L.). Issue 1 (July 2021) - Siswanti,; Anandito, R B K; Nurhartadi, E; Agustiani, R B
Abstract: The availability of healthy snacks in Indonesia is very limited, and their unhealthy consumption could lead to obesity. Snack bars are examples of snacks in the market with wheat flour being used as the raw material. However, black rice bran and sweet potato flour are local raw materials that could replace it. Therefore, the aim of this research is to obtain the best formula for snack bars using black rice bran and sweet potato flour. A Completely Randomized Design (CRD) was used in this research with one-factor, namely ratio of black rice bran and sweet potato flour (10:90, 20:80, 30:70, 40:60, 50:50) (%w/w). Furthermore, the best formulation of snack bars based on physical, chemical and sensory characteristics was F3 (30% black rice bran:70% sweet potato flour). It was composed of 6g of black rice bran, 14g of sweet potato flour, 10g of whole milk, 12g of powdered sugar, 0.25g of vanilla, 8g of egg white, 4g of liquid margarine, and 8g of water. Furthermore, it has moisture, ash, protein, fat, carbohydrates, dietary fiber, total calories, vitamins B1, and antioxidant activity of IC50 contents, namely 20.9%, 3.1%, 7.5%, 12.6%, 76.8%, 12.5%, 84.9 kkal/25 g; < 0.25 ppm and 443^g/mL, respectively. This snack bar has a hardness level of 6.8 N and higher levels of dietary fiber and antioxidant activity than the commercial ones.